Incorporación del plan estratégico financiero como herramienta para mejorar la situación económica financiera de la empresa de transportes Ave Fenix SAC., 2018 - Naranjo Rojas, Janina Lisset (2018)
The present work of investigation has as purpose demonstrate if the incorporation of the financial strategic plan is a tool to improve the economic financial situation of Empresa de Transporte Ave Fénix SAC. For the development of this investigation there took as a sample the information obtained of the different departments of the company, with which one concludes that a scheme does not exist on which programming the movements of cash, investment plans, between other expenditures, being a principal factor the lack of training of the personnel in topics of financial management and not utilization of a financial strategic plan. To be able to expire with the principal aim of the present work, first an analysis had to be realized on the operative processes and of treasury of the historical financial situation of the company, after it there are going to be designed the Financial Strategic Plan, the budgets and the strategic financiers who are going to solve the problems detected for Empresa de Transporte Ave Fénix SAC. SAC period 2018. To develop this investigation there was in use the descriptive and applied method since the information was obtained directly of the observation of the environment of the Diverse Departments of the Empresa de Transporte Ave Fénix SAC. and the calculation applied to itself of financial ratios. With the present investigation it is sought to recommend to the company to possess a Financial Strategic Plan and to keep it updated. Likewise, to qualify to his clerical staff on topics of finance and the control on the financial resources. All this with the purpose of improving the profitability of the Company and of being able to have a base for the capture of decisions on behalf of the management, looking for the growth and positioning of the company in the market.